The tendencies in the change of precipitation in Hungary - Gimesi, László (Acta Agraria Kaposváriensis, 2006)
Nowadays, the examination of the climate changes has become a central question in all fields of life, as it has an effect on different processes in economy, ecology, agriculture, hydrology, etc. The main attendant phenomenon of it is the change of weather, one of its important parameters is precipitation. Our task is the examination of the time series, consisting of the daily amount of precipitation of a 100 years in the 20th century; we analyze the amount of precipitation, its distribution in time and space, and the tendencies in the changes as well. We study the aggregate amount of precipitation, the mean in the matter of wet days, and also the deviation; furthermore, the changes in the time interval of a 100 years and the monthly distribution per year. Besides these, we also deal with the analysis of precipitation series for one and for more days. We have to take into consideration that the results we get and the conclusions we can draw from them are highly influenced by the calculation algorithms we use. We can draw different conclusions from the same starting data depending on what method we choose to use. It can be helpful in the analysis of the calculation results if we present our data graphically, in a form that can be interpreted more easily; this way we can present our results with the help of charts and 3D surface models. In the evaluation and presentation of the data we use – besides the traditional (statistical) methods – neural networks as well.